2017
DOI: 10.1016/j.clinthera.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Drugs and Medical Devices: Adverse Events and the Impact on Women’s Health

Abstract: A large number of medications and medical devices removed from the market by the US Food and Drug Administration over the past 4 decades specifically posed greater health risks to women. This article reviews the historical background of sex and gender in clinical research policy and describes several approved drugs and devices targeted for use in women that have caused major morbidity and mortality. The intended population for the medications and devices, population affected, approval process, and the basic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 77 publications
1
32
0
Order By: Relevance
“…The proportion of trials that reported results by sex or gender in this review (25%) was within the range of previously published reviews of non-veteran-specific RCTs from a similar time frame (13%-48%; Avery & Clark, 2016;Geller, Adams, & Carnes, 2006;Geller et al, 2011;Phillips & Hamberg, 2016). Certain study types, such as those evaluating pharmacologic and device interventions, may be particularly important targets for sex and gender research equity (Carey et al, 2017). In 2001, the U.S. General Accounting Office reported that 8 of 10 drugs removed from the market in the preceding years had more significant (and some potentially fatal) adverse effects for women than men (Heinrich, Gahart, Rowe, & Bradley, 2001).…”
Section: Reporting Of Results By Sex or Gendersupporting
confidence: 70%
“…The proportion of trials that reported results by sex or gender in this review (25%) was within the range of previously published reviews of non-veteran-specific RCTs from a similar time frame (13%-48%; Avery & Clark, 2016;Geller, Adams, & Carnes, 2006;Geller et al, 2011;Phillips & Hamberg, 2016). Certain study types, such as those evaluating pharmacologic and device interventions, may be particularly important targets for sex and gender research equity (Carey et al, 2017). In 2001, the U.S. General Accounting Office reported that 8 of 10 drugs removed from the market in the preceding years had more significant (and some potentially fatal) adverse effects for women than men (Heinrich, Gahart, Rowe, & Bradley, 2001).…”
Section: Reporting Of Results By Sex or Gendersupporting
confidence: 70%
“…Education & Teaching (Carey et al, 2017) and the historic exclusion of women from clinical trials and even the exclusion of female mice from pre-clinical research (Karp and Reavey, 2018) are known driving factors for why drugs fail. A study in 2001 found that of the 10 drugs withdrawn from the market since 1997, eight posed greater health risks for women than men (Heinrich, 2001).…”
Section: Epithelia and Membrane Transportmentioning
confidence: 99%
“…The recent spotlight on clinical trials and drug responses is a powerful example of why trial design and research needs to be disrupted. Sex differences in drug responses, including adverse side effects, are now recognised (Carey et al, 2017) and the historic exclusion of women from clinical trials and even the exclusion of female mice from pre-clinical research (Karp and Reavey, 2018) are known driving factors for why drugs fail. A study in 2001 found that of the 10 drugs withdrawn from the market since 1997, eight posed greater health risks for women than men (Heinrich, 2001).…”
Section: Education and Teaching Derek Scottmentioning
confidence: 99%